Congenital cytomegalovirus: association between dried blood spot viral load and hearing loss. Issue 4 (26th November 2007) - Walter, S; Atkinson, C; Sharland, M; Rice, P; Raglan, E; Emery, V C; Griffiths, P D
Abstract : Aim: To investigate the relation between cytomegalovirus (CMV) viral load on dried blood spots (DBS) from newborn biochemical screening ("Guthrie") cards, and sensorineural hearing loss (SNHL) in congenital CMV. Design: Cross-sectional study with retrospective case-note review. Setting: Seven paediatric audiology departments in the United Kingdom. Patients: 84 children, median age 7 years: 43 with known congenital CMV, 41 with unexplained SNHL. Interventions: Half a DBS was tested for CMV DNA viral load by quantitative real-time polymerase chain reaction (PCR). Main outcome measures: Pure tone average hearing thresholds (0.5–4 kHz). Results: DBS CMV DNA viral load significantly correlated with hearing thresholds for the worse and better hearing ears (Spearman's rank correlations: r = 0.445, p = 0.008 and r = 0.481, p = 0.004 respectively). Multivariable logistic regression showed that the effect of DBS viral load on the risk of SNHL remained important, when age and central nervous system involvement had been taken into account (odds ratio (OR) 2.76, 95% confidence interval (CI) 1.14 to 6.63, p = 0.024). The mean log DBS viral load was significantly higher in children with SNHL than in those with normal hearing (2.69 versus 1.64, 95% CI −1.84 to −0.27, p = 0.01). 8/35 (23%) children with unexplained SNHL tested positive for CMV DNA on DBS. One false positive result was obtained. Conclusion: The risk of SNHL increased with DBS viral load. Further studies should investigate whether DBS CMV testing has a role in identifying asymptomatic congenitally infected neonates at risk of SNHL, and whether antiviral treatment can reduce this risk.